If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -1(x + 6)(x + -8) Reorder the terms: y = -1(6 + x)(x + -8) Reorder the terms: y = -1(6 + x)(-8 + x) Multiply (6 + x) * (-8 + x) y = -1(6(-8 + x) + x(-8 + x)) y = -1((-8 * 6 + x * 6) + x(-8 + x)) y = -1((-48 + 6x) + x(-8 + x)) y = -1(-48 + 6x + (-8 * x + x * x)) y = -1(-48 + 6x + (-8x + x2)) Combine like terms: 6x + -8x = -2x y = -1(-48 + -2x + x2) y = (-48 * -1 + -2x * -1 + x2 * -1) y = (48 + 2x + -1x2) Solving y = 48 + 2x + -1x2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 48 + 2x + -1x2
| 2x-100=-62 | | -(4-y)=7(3-7y) | | 3(a+20)=81 | | 250x/4x^2 | | -q+2q+3-1+q= | | 24/4x-14/1 | | -16.6-12.9f-7.97=-17.43+10.9f | | u+3=1 | | (x-9)(2x-5)=0 | | (x-20)+x=90 | | 5b-10=3b-18 | | 20+9-2x+5x=-37 | | u_+3=1 | | 3.6y=5.4+3.37 | | 9X^4+3X^2+1=0 | | 3x^2+9x-5x-15= | | (22x-3)=(180) | | 4w^2-7w-3=0 | | 7(p+3)+p=5(p-2)-3p | | 10=3w-5 | | 11x+8=14x-7 | | (8x+20)=(180) | | 20+9-2x+5x=-57 | | 8.56+18.8h=18.8h+8.56 | | 6y+1=3y+9 | | 84=4u | | 3.6x-2.4x+4.3=12.8 | | (8x+20)=(122) | | 10x+2+4x=-54 | | 18.7d-18.7d=0 | | X^2-9x+21=7 | | -z-20=-11z-15z-20 |